A dopant-free organic hole transport material for efficient planar heterojunction perovskite solar cells1. Issue 22 (14th June 2015) - Liu, Yongsheng; Chen, Qi; Duan, Hsin-Sheng; Zhou, Huanping; Yang, Yang (Michael); Chen, Huajun; Luo, Song; Song, Tze-Bin; Dou, Letian; Hong, Ziruo; Yang, Yang
<x xml:space="preserve">Abstract</x> Planar heterojunction perovskite solar cells using a dopant-free organic hole transport material have been developed and an efficiency of 14.9% has been demonstrated.